(untitled) (Impetus, 2021)
Physical activity (PA) is an ideal means to obtain bio-psycho-social health benefits. Therefore, in this study we tried to know the reasons for the practice of PA for the interests of investigating and understanding the factors that can stimulate, promote and define their practice. A descriptive-correlational, cross-sectional study was carried out in an intentional sample of 58 people from the population of Ourense over 18 years of age. A questionnaire was used including the self-report of reasons for the practice of physical exercise. Prevention and positive health is the main reason indicated for performing PA. There is a positive association between the educational level and the frequency of PA (r = 0.382). Age is positively correlated with prevention, positive health, and health emergencies. Increased knowledge of the reasons for the practice of PA allows more effective and lasting intervention strategies to be created